An Examination of Fear of Crime: Kadikoy Example - Erkan, Nilgun Colpan; Sevin, Beril (KARE PUBL, 2018)
Fear of crime is described as a fear or anxiety of becoming a victim of a crime. The fear of crime affects the way of life of the individual, is therefore a comprehensive, complicated and an important problem. It is not only a spatial matter but is also connected to social and psychological factors. This makes the concept of fear of crime an urban phenomenon. Fear of crime is associated with crime that threatens the safe life in cities, but is also partly independent of the crime itself. According to researches, the decrease in crime rates do not lead to a decrease in fear of crime in the same parallel. This process shows that there are other factors influencing the fear of crime. In this study, fear of crime has been researched on people who live, work or are visiting Kadikoy, one of the top three safest districts in Istanbul. The study focuses on the time zone, spatial features and situations to determine causes of fear of crime. In order to be able to identify that, observations were made in the field of study and a study of 387 survey was conducted with the users of the site. In this study participants were asked what purpose and what time interval they were in Kadikoy, and they were desired to evaluate the situations and places that create fear in them. Most of the results are confirmed the issues mentioned in the international literature. By the interpreting the spatial conditions in which the users exist, it's seen that they make a risk assessment based on perception and that darkness and despair related to it increase the fear of crime. While issues such as feeling of insecurity are confirmed more by visitors, a few spatial measures were found not to have much effect on the fear of crime in Kadikoy. In addition to these, according to the results obtained from the questionnaire survey, places where measures should be taken about the fear of crime in Kadikoy have been determined and it has been tried to understand if the residents and visitors feel differently.
Keywords: Kadikoy; conditions of fear; fear of crime; spatial parameters; risk assessment; PERCEIVED SAFETY; CITY; PROSPECT; RISK; Public Administration